The problem of eco-dependent states in the area of public health (on the example of dental health) - Gordeeva, Anna Vladimirovna; SitdikovаIrina Dmitrievna; Galimova, Irina Alexandrovna; Gurevskaia, Olga Anatolievna; Usmanova, Irina Nikolaevna; Detochkina, Violetta Robertovna (Revista de la Universidad del Zulia, 2019)
An integrated approach to the examination, differentiated treatment and rehabilitation of patients with various forms of recurrent aphthae of the oral cavity (K12.0) allows increasing the effectiveness of treatment, restoring the microbial landscape characteristic of a healthy oral cavity, increasing the period of remission of the disease, and reducing the rate of relapses and the severity of clinical manifestations.The clinical manifestations of chronic recurrent aphthae of the oral cavity in residents of regions with adverse environmental factors, including those with a developed petrochemical industry, using the example of the city of Ufa, are characterized by certain manifestations, which contributes not only to a slowdown in the process of recovery and regenerative processes in the area of pathological elements on the oral mucosa. The microbiological method using modern test systems found an extremely diverse state of the microbiota of the oral cavity and its species diversity on the surface of aphthae in patients with gastrointestinal pathologies. Using the microbiological method, we determined the triggers and established the role of various microorganisms - enterococci, staphylococci, streptococci, yeast-like fungi of the genus Candida (C. albicans) and obligate anaerobes in exacerbating the clinical course of recurrent aphthae of the oral cavity. The data obtained can serve as an indication for the development of an integrated approach to examination, the development of differentiated treatment regimens and rehabilitation of patients with pathology of the gastrointestinal tract and various forms of recurrent aphthae of the oral cavity (K12.0), which will not only increase the effectiveness of local and general treatment but also restore the microbial landscape characteristic of a healthy oral cavity, increase the period of remission, reduce the rate of relapses and the severity of clinical manifestations in this category of people.